easyCD information kiosk system / Nora Izyani Abd Rahim - Abd Rahim, Nora Izyani (2000)
Everyday we read in the news about the latest discovery and invention in the Information Technology (IT) field. Since IT has an equally enormous potential to develop, this project is competent to be accepted and used at the music stores, which quantity is ever increasing. This information kiosk that utilizes Multimedia elements will give a new life and will change the public's perception of the conventional music store. Moreover, this project is a simulation of the work usually done by a shop assistant. The principal difference between asking for help from a shop assistant and from the kiosk is the method of presentation; where this kiosk uses a computer as the medium to relate the information to the customer by getting data from the database. Wide usage of computers enables the kiosk to be easily accepted by the public. From the observation that has been done, a complete system will reduce the operational cost of the music store and it actually increases the profits. This system is a compilation of the customer's demand that covers Searching, Album Review, Top Ten Albums, Virtual Shopping Cart and Data Update for Administrator.